Phytochemical and antioxidant studies of Malaysian medicinal plants syzygium polyanthum and octomeles sumatrana / Salwa Mohammed Raweh Abdullah Al-Faqeer - Mohammed Raweh Abdullah Al-Faqeer, Salwa (Institute of Graduate Studies, UiTM, 2017)
The leaves of S. polyanthum (Myrtaceae) and barks of O. sumatrana (Datiscaceae) were investigated for their chemical constituents, antioxidant and cytoprotective activities. Their aqueous extracts were first subjected to acidic hydrolysis and the organic layers were dissolved in water and partitioned using hexane, ethyl acetate (EtOAc) and n-butanol (BuOH). Six compounds (betulinic acid, ellagic acid, kaempferol, myricetin, quercetin, and β-sitosterol) were isolated and identified from the EtOAc and BuOH extracts of S. polyanthum and four compounds (quercetin, kaempferol, rutin, bryonolic acid) were purified from the n-butanol extract of O. sumatrana by means of MPLC and HPLC. The structures of the above compounds were determined by comparing their NMR and LCMS-TOF data with reported values. The structure of bryonolic acid was further confirmed by X-ray crystallography.